Green accounting dan kepemilikan saham publik terhadap kinerja keuangan: Peran islamic social reporting pada perusahaan pertambangan di Indeks Saham Syariah Indonesia - Rani, Siti Barokah; Arismaya, Anisa Dewi (Nur Science Institute, 2024)
This study analyses the effect of green accounting, Islamic social reporting and public share ownership on financial performance. This study uses panel data, with a sample of 16 mining sector companies in the 2019-2023 research period. The sampling technique in this study is purposive sampling. The data analysis method uses path analysis. The results of the study show that green accounting does not have a significant effect on financial performance, public share ownership has a positive effect on financial performance, Islamic social reporting does not affect financial performance, green accounting has a significant positive effect on Islamic social reporting, share ownership does not affect Islamic social reporting. The Islamic social reporting variable cannot mediate the effect of green accounting on financial performance. In contrast, the Islamic Social reporting variable can mediate the effect of public share ownership on financial performance.